Depletion of EREG enhances the osteo/dentinogenic differentiation ability of dental pulp stem cells via the p38 MAPK and Erk pathways in an inflammatory microenvironment - Ran Ran; Haoqing Yang; Yangyang Cao; Wanhao Yan; Luyuan Jin; Ying Zheng (BMC, 2021)
Abstract Background Epiregulin (EREG) is an important component of EGF and was demonstrated to promote the osteo/dentinogenic differentiation of stem cells from dental apical papilla (SCAPs). Whether EREG can stimulate the osteo/dentinogenic differentiation of dental pulp stem cells (DPSCs) in inflammatory environment is not clear. The purpose of the present study is to investigate the role of EREG on the osteo/dentinogenic differentiation ability of DPSCs in inflammatory environment. Methods DPSCs were isolated from human third molars. Short hairpin RNAs (shRNAs) were used to knock down EREG expression in DPSCs. Recombinant human EREG (rhEREG) protein was used in the rescue experiment. TNF-α was employed to mimic the inflammatory environment in vitro. Alkaline phosphatase (ALP) staining, Alizarin red staining, quantitative calcium analysis, and real-time RT-PCR were performed to detect osteo/dentinogenic differentiation markers and related signalling pathways under normal and inflammatory conditions. Results EREG depletion promoted the ALP activity and mineralization ability of DPSCs. The expression of BSP, DMP-1, and DSPP was also enhanced. Moreover, 50 ng/mL rhEREG treatment decreased the osteo/dentinogenic differentiation potential of DPSCs, while treatment with 10 ng/mL TNF-α for 4 h increased the expression of EREG in DPSCs. Conversely, EREG knockdown rescued the impaired osteo/dentinogenic differentiation ability caused by TNF-α treatment. Further mechanistic studies showed that EREG depletion activated the p38 MAPK and Erk signalling pathways in DPSCs under normal and inflammatory conditions. Conclusions Our results demonstrated that EREG could inhibit the osteo/dentinogenic differentiation potential of DPSCs via the p38 MAPK and Erk signalling pathways. Under inflammatory environment, EREG depletion enhanced osteo/dentinogenic differentiation potential of DPSCs by improving the expression of p-p38 MAPK and p-Erk.